PENINGKATAN PEMAHAMAN KONSEP PECAHAN MELALUI MEDIA PHET PUZZLE PADA SISWA SEKOLAH DASAR - Tegar Putra Gemilang; Rizka Novi Irmaningrum; Humairah Humairah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research was motivated by the low understanding of fraction concepts among fourth-grade students at SDN Sumberejo. The low mid-semester examination scores in the fractions topic indicate that the learning process has not been optimal, as teachers still predominantly use the lecture method, have not utilized instructional media effectively, and rarely employ innovative and engaging learning media. In addition, the lack of utilization of innovative and engaging learning media caused students to have difficulty understanding abstract fraction concepts, become less active in the learning process, and achieve low learning outcomes. Therefore, a learning medium that can increase student engagement and help make abstract concepts more concrete is needed, one of which is through the implementation of the PhET Puzzle media. The purpose of this study was to describe teacher activities, student activities, and the improvement of students' understanding of fraction concepts through the implementation of the PhET Puzzle media in fourth-grade students at SDN Sumberejo. The method used was Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 10 students. Data collection techniques included tests, observations, and documentation, while data analysis was carried out using descriptive quantitative methods to determine the improvement in students' learning outcomes. The results showed that the implementation of the PhET Puzzle media was able to improve both student activity and conceptual understanding. Teacher activity increased from 60% in Cycle I to 90% in Cycle II, while student activity increased from 58.75% to 90%. In addition, students' learning mastery improved from 20% in Cycle I to 80% in Cycle II. Therefore, it can be concluded that the use of the PhET Puzzle media is effective in improving the understanding of fraction concepts among fourth-grade students at SDN Sumberejo. ABSTRAK Penelitian ini dilatar belakangi oleh rendahnya pemahaman konsep pecahan pada siswa kelas IV SDN Sumberejo. Rendahnya nilai ulangan tengah semester pada materi pecahan menunjukkan bahwa pembelajaran masih kurang optimal karena guru masih dominan menggunakan metode ceramah, belum memanfaatkan media pembelajaran, dan jarang menggunakan media yang inovatif serta menarik. Akibatnya, siswa mengalami kesulitan dalam memahami konsep pecahan, kurang aktif dalam proses pembelajaran, dan hasil belajar yang diperoleh masih rendah. Oleh karena itu, diperlukan suatu media pembelajaran yang mampu meningkatkan keterlibatan siswa serta membantu memahami konsep abstrak menjadi lebih konkret, salah satunya melalui penerapan media PhET Puzzle. Tujuan penelitian ini adalah untuk mendeskripsikan aktivitas guru, aktivitas siswa, serta peningkatan pemahaman konsep pecahan melalui penerapan media PhET Puzzle pada siswa kelas IV SDN Sumberejo. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian berjumlah 10 siswa. Teknik pengumpulan data menggunakan tes, observasi, dan dokumentasi, sedangkan analisis data dilakukan secara deskriptif kuantitatif untuk mengetahui peningkatan hasil belajar siswa. Hasil penelitian menunjukkan bahwa penerapan media PhET Puzzle dapat meningkatkan aktivitas dan pemahaman konsep siswa. Aktivitas guru meningkat dari 60% pada siklus I menjadi 90% pada siklus II, sedangkan aktivitas siswa meningkat dari 58,75% menjadi 90%. Selain itu, ketuntasan belajar siswa juga mengalami peningkatan dari 20% pada siklus I menjadi 80% pada siklus II. Dengan demikian, dapat disimpulkan bahwa penerapan media PhET Puzzle efektif dalam meningkatkan pemahaman konsep pecahan pada siswa kelas IV SDN Sumberejo.